PEMANFAATAN MEDIA SOSIAL TIK TOK SEBAGAI MEDIA KAMPANYE GERAKAN CUCI TANGAN DI INDONESIA UNTUK MENCEGAH COVID-19 - Togi Prima Hasiholan; Rezki Pratami; Umaimah Wahid (LPPM Abdurrab Pekanbaru, 2020)
Indonesia, which is 64.8% of the population, has used the Internet and 160 million people are social media users, making Indonesia a promising market by social media industry players, such as the Tik Tok application. In 2020 the Tik Tok application became a popular culture in Indonesia, because the Indonesian people would know this application and become its user. The popularity of Tik Tok in Indonesia became an ideal medium by the World Health Organization (WHO) which campaigns for the correct hand washing movement to break the transmission of the COVID Virus -19 or known by the name of corona by producing videos and hashtags #safehands challenge in the Tik Tok application, then the creators produce their own version of video content and add hashtags #safehands challenge to follow this challenge. Campaigning via video with this #safehands challenge hashtag watched a lot, but there are some points that underlie which videos are most watched, liked and shared by Tik Tok users.